Cochlear implantation in a subject with a narrow facial recess: Importance of preoperative radiological findings. (3rd May 2016) - Sennaroglu, Levent; Tahir, Emel
Abstract : Objective : This case report aims to emphasize the importance of preoperative computed tomography to evaluate the anatomy of the facial recess (FR) in order to prevent complications during cochlear implantation (CI) and to discuss alternative surgical approaches for the management of a narrow FR. Failure to notice this anomaly may result in facial nerve (FN) injury or inability to complete CI. Case presentation : A 50-year-old female with bilateral sensorineural hearing loss presented for CI. High-resolution CT (HRCT) demonstrated a narrow FR; specifically the space between the vertical segment of the FN and external auditory canal (EAC) was narrow. A section of the EAC was removed to obtain adequate exposure and was repaired with a cartilage graft following CI. Conclusion : CI surgery may be difficult in patients with a narrow FR. Such surgical difficulty could be avoided if cochlear implant surgeons have adequate preoperative radiological imaging to evaluate the anatomy of the temporal bone. HRCT is the only modality that can detect this abnormality preoperatively. If the surgeon identifies this abnormality on preoperative HRCT, an alternative surgical technique could be used.